PENGARUH JUMLAH DATA DAN LOKASI TRAFFIC COUNT TERHADAP ESTIMASI MATRIKS ASAL-TUJUAN KOTA BANDAR LAMPUNG BERDASARKAN ARUS LALU LINTAS - Wiwit Tri Rahayu (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
The more data traffic count using in process with unconventional methods, will estimate the better OD matrix, but it spend a lot of times, effort, and cost. Efficiency can be done by finding the amount of data and point the exact location, making it more effective in terms of time and costs but still produce an optimal estimate of O-D Matrix. The use of 42 traffic count produce estimate of OD Matrix model (100%) with R-square is 0,3114 for the current level. Scenarios is done by selecting roads with the lowest flow rate, 2 data for each scenario. Selection of input data traffic flow yield of the 13 scenarios, each of scenarios produce estimate of O-D Matrix with variation Rsquare. R-square of 0,9517 for linear trend line shows the amount of data has a tremendous influence in the decline in the value of R-square for the current level. Inconsiderably the condition of dependence, inconsistency, and the proportion movement make estimate of O-D Matrix has not been seen significantly. The optimum number of traffic count data is about 32 traffic count data, or about 76,19% of the total data traffic count (100%). Roads that could be recommended to input data to estimate O-D Matrix traffic count of more effective and efficient based on the study of the road with a large amount of movement of vehicles, roads with a large proportion of the movement of traffic between the zones, and roads are not only through private vehicles but also by public transport.